A lithium bis(fluorosulfonyl)imide composition and preparation method thereof

Through the salt exchange reaction between KFSI and lithium nitrate, combined with filtration and washing steps, a lithium difluorosulfonimide composition with an appropriate nitrate content was prepared, which solved the battery stability and corrosion problems in the prior art and improved the battery's Cycling performance and safety performance.

CN116495711BActive Publication Date: 2024-12-27HUNAN FLUOPONT NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210062643.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-19
Publication Date
2024-12-27
Estimated Expiration
2042-01-19

AI Technical Summary

Technical Problem

In the existing preparation method for lithium difluorosulfonimide, there are problems of separation difficulties and high impurity content, and the electrodes are corroded in the lithium battery electrolyte, deteriorating the battery stability.

Method used

The salt exchange reaction was carried out by KFSI and lithium nitrate, and the lithium bisfluorosulfonimide composition with nitrate content of 20ppm-1000ppm was prepared to inhibit the solution by filtration, cationic impurity removal, pure water washing and non-polar organic solvent dispersed crystallization. Corrosion of the electrode current collector.

Benefits of technology

It significantly reduces the long-term circulation volume expansion rate of the battery, improves the stability and safety performance of the battery, extends the circulation life of the aluminum current collector, and reduces battery side reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

In order to solve the problem in the prior art that lithium bis(fluorosulfonyl)imide is used in lithium battery electrolyte to corrode electrodes and deteriorate battery stability, the present invention provides a lithium bis(fluorosulfonyl)imide composition and a preparation method thereof. The preparation method comprises the steps of reacting KFSI and lithium nitrate to obtain the lithium bis(fluorosulfonyl)imide composition. The prepared lithium bis(fluorosulfonyl)imide composition contains 20ppm-1000ppm of nitrate. When the composition is used in lithium secondary battery electrolyte, a trace amount of nitrate inhibits the corrosion of lithium bis(fluorosulfonyl)imide on electrode current collectors, greatly reduces the corrosion of aluminum current collectors, improves the cycle life thereof, reduces the long-term cycle volume expansion rate of the battery, and improves the battery stability and safety performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of bisfluorosulfonyl imide salts, and specifically relates to a bisfluorosulfonyl imide lithium composition and a preparation method thereof. Background Art

[0002] Lithium bis(fluorosulfonyl)imide is abbreviated as LiFSI, and its chemical formula is LiN(SO 2 F) 2 Lithium bis(fluorosulfonyl)imide has high temperature resistance and excellent low temperature performance. It also has the advantages of good stability in water and more environmentally friendly. It is widely used in the electrolyte of lithium-ion batteries. It can effectively reduce the high and low temperature resistance of the SEI layer formed on the electrode surface at low temperatures, and reduce the capacity loss of lithium-ion batteries during storage, thereby providing high-capacity batteries and improving the electrochemical performance of batteries. Lithium bis(fluorosulfonyl)imide LiFSI is a key high-performance electrolyte material in new energy devices such as lithium-ion batteries and supercapacitors, and has high industrial application value.

[0003] Most LiFSI synthesis methods are to first synthesize bis(chlorosulfonyl)imide HClSI, which is then reacted with a fluorometal salt MFx to prepare the corresponding bis(fluorosulfonyl)imide salt intermediate, which is then reacted with lithium hydroxide LiOH or lithium carbonate Li 2 CO 3 LiFSI is prepared by cation exchange, such as patents US2013331609, US2012041233, EP2415757, US2011034716, CN101747242A. The defect of these methods is that it is difficult to continue completely after the exchange reaches equilibrium, and the unreacted intermediate is difficult to be completely separated from LiFSI, so that high-quality products cannot be obtained. In addition, there is a literature report that lithium perchlorate and potassium bis(fluorosulfonyl)imide are used to undergo a double decomposition reaction in an acetonitrile system to prepare lithium bis(fluorosulfonyl)imide. The process uses highly oxidizing lithium perchlorate, and the generated by-product potassium perchlorate is difficult to completely remove. There is a problem of explosiveness and high impurity content, so it cannot be used in production. Therefore, how to produce LiFSI with low impurity content and harmless impurities has become a problem faced by various manufacturers.

[0004] Lithium bis(fluorosulfonyl)imide (LiFSI) is used as a lithium salt or additive in lithium battery electrolytes. The prepared secondary batteries have good thermal stability and can improve the safety performance of the batteries. However, when the molar ratio of lithium bis(fluorosulfonyl)imide (LiFSI) is large, it will corrode the electrode collector during battery charging and discharging, causing side reactions and deteriorating the stability of lithium-ion secondary batteries. Summary of the invention

[0005] Aiming at the problems that the lithium bis(fluorosulfonyl)imide is difficult to separate and contains a lot of impurities in the prior art lithium bis(fluorosulfonyl)imide preparation method, and the lithium bis(fluorosulfonyl)imide is used in the lithium battery electrolyte to corrode the electrode and deteriorate the battery stability, the present invention provides a lithium bis(fluorosulfonyl)imide composition and a preparation method thereof.

[0006] In one aspect, the present invention provides a method for preparing a lithium bis(fluorosulfonyl)imide composition, comprising the following steps:

[0007] 1) KFSI is dissolved in solvent c to obtain solution A;

[0008] 2) dissolving lithium nitrate in solvent e to obtain solution B;

[0009] 3) Solution A and Solution B are mixed and stirred, and then heated to react. After the reaction is completed, the mixture is filtered to obtain a crude solution of lithium bis(fluorosulfonyl)imide;

[0010] 4) passing the crude lithium bis(fluorosulfonyl)imide solution in step 3) through a cationic resin to remove cationic impurities, and performing a first concentration and drying to obtain a crude lithium bis(fluorosulfonyl)imide solid;

[0011] 5) The crude solid of lithium bis(fluorosulfonyl)imide in step 4) is dissolved in solvent d to obtain solution D, which is then filtered and washed with pure water, the organic phase is collected and concentrated and dried for a second time, and finally a non-polar organic solvent is added to disperse and crystallize to obtain a lithium bis(fluorosulfonyl)imide composition with a nitrate content of 20 ppm to 1000 ppm.

[0012] Preferably, in the step 1), the mass percentage of KFSI is 10% to 80% based on the mass of solution A being 100%;

[0013] In the step 2), the mass percentage of lithium nitrate is 5% to 50% based on the mass of solution B being 100%;

[0014] The heating temperature in step 3) is 20°C to 60°C.

[0015] Preferably, the heating temperature in step 3) is 45°C to 60°C.

[0016] Preferably, in the step 5), based on 100% of the mass of the solution D, the mass percentage of the lithium bis(fluorosulfonyl)imide is 5% to 80%;

[0017] In the step 5), the crude solid of lithium bis(fluorosulfonyl)imide is dissolved in solvent d at a dissolution temperature of 10° C. to 80° C.

[0018] Preferably, in the step 5), based on 100% of the mass of the solution D, the mass percentage of the lithium bis(fluorosulfonyl)imide is 15% to 50%;

[0019] In the step 5), the crude solid of lithium bis(fluorosulfonyl)imide is dissolved in the solvent d at a dissolution temperature of 20° C. to 60° C., preferably 45° C. to 60° C.

[0020] Preferably, the first concentration and drying in step 4) comprises first concentration under normal pressure and then concentration under reduced pressure;

[0021] The mass of pure water in the pure water washing in step 5) is 0.5 to 5 times the mass of the crude solid product of lithium bis(fluorosulfonyl)imide; the number of times of the pure water washing is ≥ 1, and the pure water washing step is to further remove potassium nitrate dissolved in water and reduce the nitrate content of the lithium bis(fluorosulfonyl)imide composition;

[0022] After the second concentration and drying in step 5), the mass percentage of lithium bis(fluorosulfonyl)imide is 60% to 90% based on the mass of the lithium bis(fluorosulfonyl)imide concentrated solution as 100%; the mass of the non-polar organic solvent added is 0.5 to 3 times the mass of the lithium bis(fluorosulfonyl)imide concentrated solution;

[0023] In the step 5), a membrane filter is used for filtration, and the pore size of the membrane filter includes at least one of 2um, 1um or 0.1-0.5um.

[0024] The step 5 can also be used to remove other impurity anions contained in the crude lithium bis(fluorosulfonyl)imide product. These impurity anions can be introduced through raw materials or equipment. The anions include but are not limited to carbonate anions, bicarbonate anions, sulfate anions, oxalate anions, acetate anions, formate anions, hydroxide anions, phosphate anions, hydrogen phosphate anions, dihydrogen phosphate anions, and halogen anions.

[0025] Preferably, the solvent c and the solvent e each independently include one or more of anhydrous methanol, ethanol, acetone, ether, ethyl acetate, butyl acetate, sec-butyl acetate, amyl acetate, n-hexyl acetate, dimethyl carbonate, and ethyl methyl carbonate;

[0026] The solvent d is a hydrophobic polar aprotic solvent, including one or more of a carbonate solvent or a nitrile solvent;

[0027] The cationic resin includes a strong acid resin;

[0028] The non-polar organic solvent includes one or more of dichloromethane, dichloroethane, toluene, xylene, and cyclohexane. On the other hand, the present invention provides a lithium bisfluorosulfonyl imide composition prepared by the above-mentioned lithium bisfluorosulfonyl imide composition preparation method, comprising lithium bisfluorosulfonyl imide and nitrate, and based on 100% of the mass of the lithium bisfluorosulfonyl imide composition, the mass percentage of the lithium bisfluorosulfonyl imide is ≥99%.

[0029] Preferably, based on 100% by mass of the lithium bis(fluorosulfonyl)imide composition, the content of the nitrate ion is 20 ppm to 500 ppm.

[0030] Preferably, based on 100% by mass of the lithium bis(fluorosulfonyl)imide composition, the mass content of the lithium bis(fluorosulfonyl)imide is ≥ 99.8%.

[0031] Preferably, the lithium bis(fluorosulfonyl)imide composition further comprises K + , H 2 O, an organic solvent, based on 100% by mass of the lithium bis(fluorosulfonyl)imide composition, the K + ≤5ppm, the H 2 O≤50ppm, and the organic solvent≤1500ppm.

[0032] Beneficial effects of the present invention:

[0033] The present invention provides a method for preparing a lithium bis(fluorosulfonyl)imide composition. The reactants are KFSI and lithium nitrate for salt exchange reaction to prepare a lithium bis(fluorosulfonyl)imide composition. Insoluble matter and cationic impurities are first filtered to remove them. Then, the prepared lithium bis(fluorosulfonyl)imide crude product is fixedly dissolved in a solvent d, filtered, washed with pure water, and potassium nitrate is further removed to finally obtain a lithium bis(fluorosulfonyl)imide composition having a nitrate content of 20ppm-1000ppm. When the lithium bis(fluorosulfonyl)imide containing 20ppm-1000ppm nitrate is applied to a lithium secondary battery electrolyte, the nitrate can be reduced at the electrode interface to form nitrogen-containing alkali metal oxides and / or alkali metal nitrides and other substances, thereby inhibiting the corrosion of the lithium bis(fluorosulfonyl)imide to the electrode current collector. The prepared lithium secondary battery can significantly reduce the corrosion of the aluminum current collector or reduce the corrosion of the aluminum current collector to zero, thereby improving its cycle life, reducing the battery's long-term cycle volume expansion rate, and improving the battery's stability and safety performance. DETAILED DESCRIPTION

[0034] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0035] On the one hand, an embodiment of the present invention provides a method for preparing a lithium bis(fluorosulfonyl)imide composition, comprising the following steps:

[0036] 1) KFSI is dissolved in solvent c to obtain solution A;

[0037] 2) dissolving lithium nitrate in solvent e to obtain solution B;

[0038] 3) Solution A and Solution B are mixed and stirred, and then heated to react. After the reaction is completed, the mixture is filtered to obtain a crude solution of lithium bis(fluorosulfonyl)imide;

[0039] 4) passing the crude lithium bis(fluorosulfonyl)imide solution in step 3) through a cationic resin to remove cationic impurities, and performing a first concentration and drying to obtain a crude lithium bis(fluorosulfonyl)imide solid;

[0040] 5) The crude solid of lithium bis(fluorosulfonyl)imide in step 4) is dissolved in solvent d to obtain solution D, followed by filtration, water washing, collection of the organic phase, and concentration and drying for a second time, and finally a non-polar organic solvent is added for dispersion and crystallization to obtain a lithium bis(fluorosulfonyl)imide composition having a nitrate content of 20 ppm to 1000 ppm.

[0041] In the preparation method of lithium bis(fluorosulfonyl)imide composition, potassium bis(fluorosulfonyl)imide and lithium nitrate are used to prepare lithium bis(fluorosulfonyl)imide, and a lithium bis(fluorosulfonyl)imide composition containing lithium bis(fluorosulfonyl)imide and 20ppm-1000ppm nitrate can be obtained. In step 3), the solution after the reaction is filtered to remove insoluble substances such as potassium nitrate, thereby reducing the nitrate content of the lithium bis(fluorosulfonyl)imide composition; step 4) is a method for further purifying the lithium bis(fluorosulfonyl)imide composition, wherein the filtrate of the crude lithium bis(fluorosulfonyl)imide is subjected to cation removal to reduce the cations such as K in the lithium bis(fluorosulfonyl)imide composition. + content; in step 5), after the crude lithium bis(fluorosulfonyl)imide is dissolved in solvent d, it is filtered and washed with water. Since potassium nitrate is insoluble in solvent d and is easy to dissolve in water, water washing can further remove the potassium nitrate soluble in water, thereby further reducing the content of nitrate in the composition. The present invention prepares the lithium bis(fluorosulfonyl)imide composition with low impurity ion content, does not increase battery side reactions, and does not deteriorate battery performance. The crude solid of lithium bis(fluorosulfonyl)imide is dissolved, filtered, washed, concentrated and dried, and dispersed and crystallized for purification. The separation method of lithium bis(fluorosulfonyl)imide is simple, and a lithium bis(fluorosulfonyl)imide composition with low impurity content and trace nitrate is obtained. The prepared lithium bis(fluorosulfonyl)imide composition is applied to lithium battery electrolyte, and nitrate with a content of 20ppm-1000ppm can be reduced at the electrode interface to form nitrogen-containing alkali metal oxides and / or alkali metal nitrides and other substances, thereby inhibiting the corrosion of lithium bis(fluorosulfonyl)imide to the electrode current collector, improving the battery cycle performance, reducing the battery long-term cycle volume expansion rate, and improving the battery safety performance and stability performance.

[0042] In some embodiments, in step 1), the mass percentage of KFSI is 10% to 80% based on the mass of solution A as 100%;

[0043] In the step 2), the mass percentage of lithium nitrate is 5% to 50% based on the mass of solution B being 100%;

[0044] The heating reaction temperature in step 3) is 20°C to 60°C.

[0045] Preferably, the heating reaction temperature in step 3) is 45°C-60°C.

[0046] The mass percentage of KFSI in solution A is 10% to 80%, and the mass percentage of lithium nitrate in solution B is 5% to 50%. Solution A and solution B are mixed; the mixing method can be dropwise adding solution A to solution B, or dropwise adding solution B to solution A, or directly mixing.

[0047] The heating reaction temperature for preparing lithium bis(fluorosulfonyl)imide from KFSI and lithium nitrate is 20-60°C. The salt exchange reaction can be carried out at room temperature (above 20°C), or the reaction solution can be heated to 20-60°C for salt exchange reaction. Preferably, the heating temperature is 45-60°C.

[0048] In some embodiments, solvent c and solvent e each independently include one or more of anhydrous methanol, ethanol, acetone, ethyl ether, ethyl acetate, butyl acetate, sec-butyl acetate, amyl acetate, n-hexyl acetate, dimethyl carbonate, and ethyl methyl carbonate.

[0049] In some embodiments, the cationic resin in step 4) includes a strong acid resin. The cationic resin is used to remove cationic impurities from the crude lithium bis(fluorosulfonyl)imide solution to remove potassium ions and reduce the content of cationic impurities in the lithium bis(fluorosulfonyl)imide composition.

[0050] Strong acid resins contain a large number of strong acid groups, such as sulfonic acid groups -SO 3 H, which easily dissociates into hydrogen ions in the solution, is strongly acidic. After the resin dissociates, the negatively charged groups in the body, such as SO 3 2- It can adsorb and combine with other cations in the solution. These two reactions cause the hydrogen ions in the resin to exchange with the cations in the solution, thereby further removing cationic impurities.

[0051] In some embodiments, the solvent d is a hydrophobic polar aprotic solvent, including carbonate solvents, nitrile solvents, and the like.

[0052] In some preferred embodiments, the solvent d comprises one or more of dimethyl carbonate, ethyl methyl carbonate, butyl acetate, sec-butyl acetate, amyl acetate, isoamyl acetate, n-hexyl acetate, and phenyl acetate.

[0053] Based on 100% of the mass of the solution D, the mass percentage of the lithium bis(fluorosulfonyl)imide is 5% to 80%; in some preferred embodiments, based on 100% of the mass of the solution D, the mass percentage of the lithium bis(fluorosulfonyl)imide is 15% to 50%.

[0054] The crude solid lithium bis(fluorosulfonyl)imide obtained in step 4) is dissolved in solvent d, wherein the mass percentage of lithium bis(fluorosulfonyl)imide is 5% to 80% based on 100% mass of the solution D, and the mass percentage of lithium bis(fluorosulfonyl)imide is preferably 15% to 50%. The crude solid lithium bis(fluorosulfonyl)imide is dissolved in solvent d, and potassium nitrate generated by the salt exchange reaction is insoluble in organic solvents, and the nitrate content in the lithium bis(fluorosulfonyl)imide composition can be further reduced by this step.

[0055] The crude solid of lithium bis(fluorosulfonyl)imide is dissolved in solvent d, wherein the mass percentage of lithium bis(fluorosulfonyl)imide can be 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%. The mass percentage of lithium bis(fluorosulfonyl)imide is related to its solubility in solvent d. The higher the mass percentage of lithium bis(fluorosulfonyl)imide, the lower the mass of solvent d, the weaker the dissolving ability, and the higher the organic solvent content of the prepared lithium bis(fluorosulfonyl)imide composition.

[0056] In some embodiments, the step 5) wherein the crude solid of lithium bis(fluorosulfonyl)imide is dissolved in solvent d is performed at a dissolution temperature of 10°C to 80°C.

[0057] In some preferred embodiments, the step 5) wherein the crude solid of lithium bis(fluorosulfonyl)imide is dissolved in the solvent d has a dissolution temperature of 20°C to 60°C.

[0058] The dissolution temperature affects the solubility of the solvent d in dissolving the crude solid of lithium bis(fluorosulfonyl)imide. The preferred dissolution temperature is between 20° C. and 60° C., which helps to improve the solubility of the solvent d and reduce the impurity content of the lithium bis(fluorosulfonyl)imide composition.

[0059] In some embodiments, in step 5), solution D is filtered to remove some impurities in the crude solid of lithium bis(fluorosulfonyl)imide; wherein the filtration is preferably performed using a membrane filter, and the membrane pore size in the membrane filter can be selected from at least one of 2 μm, 1 μm, or 0.1 to 0.5 μm. By selecting a membrane filter with a membrane pore size of at least one of 2 μm, 1 μm, or 0.1 to 0.5 μm to filter solution D, impurities with a pore size larger than the membrane pore size are removed, thereby reducing the impurity content.

[0060] In some preferred embodiments, the pore size of the membrane filter selected for filtration in step 5 is preferably 0.1-0.5 μm.

[0061] In some embodiments, the mass of water in the water washing in step 5) is 0.5 to 5 times the mass of the crude solid of lithium bis(fluorosulfonyl)imide, and the number of water washings is greater than or equal to 1 time; the water washing method is preferably continuous reverse phase extraction washing.

[0062] By washing with water, water-soluble impurities in the crude solid of lithium bis(fluorosulfonyl)imide can be removed, such as potassium nitrate soluble in water, thereby further reducing the content of nitrate in the composition. The water washing method is preferably continuous reverse phase extraction washing, and multiple washings can save time, improve efficiency, and increase the purity of the crude solid of lithium bis(fluorosulfonyl)imide.

[0063] In some embodiments, in step 5), after the second concentration and drying, based on the mass of the lithium bis(fluorosulfonyl)imide concentrated solution being 100%, the mass percentage of lithium bis(fluorosulfonyl)imide is 60% to 90%.

[0064] In some embodiments, in step 5), the mass of the non-polar organic solvent added is 0.5 to 3 times the mass of the lithium bis(fluorosulfonyl)imide concentrated solution.

[0065] By using the principle that similarity is compatible between the non-polar organic solvent and the solvent d, the non-polar organic solvent is compatible with the solvent d, and the lithium bisfluorosulfonyl imide composition is dispersed and crystallized to obtain a purified lithium bisfluorosulfonyl imide composition.

[0066] The non-polar organic solvent includes one or more of dichloromethane, dichloroethane, toluene, xylene, and cyclohexane.

[0067] On the other hand, an embodiment of the present invention provides a lithium bisfluorosulfonyl imide composition, comprising lithium bisfluorosulfonyl imide and nitrate, wherein the content of nitrate is 20ppm to 1000ppm based on 100% by mass of the lithium bisfluorosulfonyl imide composition, and the mass content of the lithium bisfluorosulfonyl imide is ≥99%.

[0068] In the prior art, lithium hexafluorophosphate is generally used as lithium salt in the non-aqueous electrolyte of lithium batteries. However, lithium hexafluorophosphate has poor stability and decomposes during the battery charge and discharge cycle, reducing battery performance. In order to solve this problem, lithium bis(fluorosulfonyl)imide (LiFSI) is added to the non-aqueous electrolyte. However, when the molar content of LiFSI is low, lithium bis(fluorosulfonyl)imide does not significantly improve the safety performance of lithium secondary batteries, and does not significantly improve the stability performance of lithium secondary batteries. When the molar content of lithium bis(fluorosulfonyl)imide added to the non-aqueous electrolyte is large, lithium bis(fluorosulfonyl)imide continuously corrodes the electrode current collector during the battery cycle, the battery side reactions increase, and the battery stability decreases. The inventors have found through a large number of studies that trace amounts of nitrate can inhibit the corrosion of lithium bis(fluorosulfonyl)imide on the electrode current collector.

[0069] The lithium bis(fluorosulfonyl)imide composition provided by the present invention contains lithium bis(fluorosulfonyl)imide and nitrate. When applied to an electrolyte, the content of nitrate is 20ppm to 1000ppm. A trace amount of nitrate can be reduced at the electrode interface to form nitrogen-containing alkali metal oxides and / or alkali metal nitrides and other substances, thereby inhibiting the corrosion of the electrode current collector by lithium bis(fluorosulfonyl)imide. In addition, most of the nitrate in the composition may be in the form of lithium nitrate. Since lithium nitrate itself is unstable and belongs to an explosive substance, from the perspective of battery safety, the content of nitrate cannot be higher than 1000ppm. If the nitrate content in the electrolyte is too high, the prepared battery will have too many nitrogen-containing alkali metal oxides and / or alkali metal nitrides and other substances reduced at the electrode interface after multiple charge and discharge cycles, and there is a possibility of further reduction to low-boiling nitrogen oxides (such as nitrogen dioxide, nitric oxide), increasing the internal pressure of the battery, increasing the volume expansion rate of the battery, generating a risk of bulging, and reducing the safety performance of the battery.

[0070] When the lithium bis(fluorosulfonyl imide) composition provided by the present invention is applied to a lithium secondary battery electrolyte, the prepared lithium secondary battery can significantly reduce the corrosion of the aluminum current collector or reduce the corrosion of the aluminum current collector to zero, thereby increasing its cycle life, increasing the battery stability, and improving the safety performance of the battery. In the lithium secondary battery electrolyte, when the molar content of the lithium bis(fluorosulfonyl imide) composition is relatively large, a trace amount of nitrate ions inhibits the corrosion of the lithium bis(fluorosulfonyl imide) on the electrode current collector, thereby improving the cycle performance, stability, and safety performance of the battery.

[0071] In some preferred embodiments, based on 100% by mass of the lithium bis(fluorosulfonyl)imide composition, the content of nitrate is 20 ppm to 500 ppm.

[0072] The inventors have found through a large number of experiments that trace amounts of nitrate in the lithium bis(fluorosulfonyl)imide composition can be reduced at the electrode interface to form nitrogen-containing alkali metal oxides and / or alkali metal nitrides and other substances, thereby inhibiting the corrosion of the electrode current collector by lithium bis(fluorosulfonyl)imide. When the nitrate content is 20ppm to 500ppm, the battery cycle life is longer, the battery stability is better, and the battery safety performance is effectively improved.

[0073] Further, in the lithium bis(fluorosulfonyl)imide composition, the nitrate content is 20ppm, 30ppm, 40ppm, 50ppm, 60ppm, 70ppm, 80ppm, 90ppm, 100ppm, 110ppm, 120ppm, 130ppm, 140ppm, 150ppm, 160ppm, 170ppm, 180ppm, 190ppm, 200ppm, 210ppm, 220ppm, 230ppm, 240ppm, 250ppm, 260ppm, 300ppm, 310ppm, 320ppm, 350ppm, 360ppm, 370ppm, 380ppm, 390ppm, 400ppm, 410ppm, 420ppm, 430ppm, 440ppm, 450ppm, 460ppm, 470ppm, 480ppm, and 500ppm.

[0074] In some preferred embodiments, in the lithium bisfluorosulfonyl imide composition, based on 100% by mass of the lithium bisfluorosulfonyl imide composition, the content of lithium bisfluorosulfonyl imide is ≥ 99.8%.

[0075] Lithium bis(fluorosulfonyl imide) is used in lithium battery electrolytes. It has a wider operating temperature range and better thermal stability, thereby providing safety performance for lithium-ion batteries. Lithium bis(fluorosulfonyl imide) is used in lithium battery electrolytes. It maintains good compatibility with positive and negative electrode materials and can significantly improve the high and low temperature performance of lithium-ion batteries. The higher the content of lithium bis(fluorosulfonyl imide) in the lithium bis(fluorosulfonyl imide) composition, the more it can improve the thermal stability, safety, cycle performance and high and low temperature performance of lithium batteries.

[0076] In some preferred embodiments, the lithium bis(fluorosulfonyl)imide composition further comprises K + , H 2 O and organic solvents;

[0077] Based on 100% by mass of the lithium bis(fluorosulfonyl)imide composition, the K + ≤5ppm, the H 2 O≤50ppm;

[0078] The organic solvent is ≤1500ppm.

[0079] In the lithium bis(fluorosulfonyl)imide composition provided by the present invention, K + , H 2 O. The organic solvent has a low impurity content, and the composition is applied to the electrolyte without affecting the battery performance.

[0080] In order to further illustrate the technical solution of the present invention, the present invention is further elaborated and described below in conjunction with embodiments.

[0081] Example 1

[0082] The preparation method of the lithium bis(fluorosulfonyl)imide composition comprises the following steps:

[0083] Step 1) Dissolve KFSI in solvent c ethanol at room temperature to prepare a solution A with a concentration of 50%;

[0084] Step 2) dissolving lithium nitrate in solvent e ethanol at room temperature to prepare a solution B with a concentration of 50%;

[0085] Step 3) directly mixing solution A and solution B, stirring at room temperature after mixing, and then heating reaction, the heating reaction temperature is 30° C. After the reaction is completed, the reaction solution is filtered to remove insoluble matter such as potassium nitrate, the filtered solid is centrifuged and dried, and the filtrate is a crude solution of lithium bis(fluorosulfonyl)imide;

[0086] Step 4) the crude lithium bis(fluorosulfonyl)imide solution obtained in step 3) is passed through a pre-treated strong acid resin to remove cation impurities, and a crude lithium bis(fluorosulfonyl)imide solution with qualified cations is obtained after the operation is completed; the crude lithium bis(fluorosulfonyl)imide solution with qualified cations is first concentrated at normal pressure and then concentrated under reduced pressure, and then dried to obtain a crude lithium bis(fluorosulfonyl)imide solid;

[0087] Step 5) dissolving the crude solid of lithium bis(fluorosulfonyl)imide in step 4) into solvent methyl ethyl carbonate to obtain solution D, wherein the dissolution temperature is 60°C and the concentration percentage of lithium bis(fluorosulfonyl)imide in solution D is 60%. A membrane filter with a pore size of 0.5 μm is selected to filter solution D. After solid-liquid separation, the obtained filtrate is washed with pure water in a continuous reverse phase extraction washing manner to further remove potassium nitrate and reduce the nitrate content, wherein the mass of pure water is 2 times the mass of the crude solid of lithium bis(fluorosulfonyl)imide, and washing is performed twice. After washing, the organic phase is collected and concentrated and dried to obtain a lithium bis(fluorosulfonyl)imide concentrated solution with a solution percentage concentration of 80%. Adding a non-polar organic solvent xylene to the lithium bis(fluorosulfonyl)imide concentrated solution with a solution percentage concentration of 80%, wherein the mass of xylene added is 1.5 times the mass of the lithium bis(fluorosulfonyl)imide concentrated solution; and dispersing and crystallizing to obtain a lithium bis(fluorosulfonyl)imide composite.

[0088] Embodiment 2-4

[0089] The difference between Example 2-4 and Example 1 is that the mass ratio of pure water to the mass of crude solid lithium bis(fluorosulfonyl)imide in the pure water washing step in step 5 is different, and the number of washings is different. The specific ratio of the mass of crude solid lithium bis(fluorosulfonyl)imide to the mass of pure water and the number of washings are shown in Table 1; the rest is the same as Example 1.

[0090] Comparative Example 1

[0091] Step 1) Dissolve KFSI in solvent c ethanol at room temperature to prepare a solution A with a concentration of 50%;

[0092] Step 2) dissolving lithium nitrate in solvent e ethanol at room temperature to prepare a solution B with a concentration of 50%;

[0093] Step 3) directly mixing solution A and solution B, stirring at room temperature after mixing, and then heating reaction, the heating reaction temperature is 30° C. After the reaction is completed, the reaction solution is filtered to filter out insoluble matter, the filtered solid is centrifuged and dried, and the filtrate is a crude solution of lithium bis(fluorosulfonyl)imide;

[0094] Step 4) concentrating the crude lithium bis(fluorosulfonyl)imide solution at normal pressure and then at reduced pressure, and then drying to obtain a crude lithium bis(fluorosulfonyl)imide solid;

[0095] Step 5) dissolving the crude solid of lithium bis(fluorosulfonyl)imide in step 4) into solvent d ethyl methyl carbonate to obtain solution D, wherein the dissolution temperature is 60°C and the concentration percentage of lithium bis(fluorosulfonyl)imide in solution D is 60%. Select a membrane filter with a pore size of 0.5 μm to filter solution D, collect the organic phase after solid-liquid separation, and concentrate and dry it to obtain a lithium bis(fluorosulfonyl)imide concentrated solution with a solution percentage concentration of 80%. Add a non-polar organic solvent xylene to the lithium bis(fluorosulfonyl)imide concentrated solution with a solution percentage concentration of 80%, wherein the mass of xylene added is 1.5 times the mass of the lithium bis(fluorosulfonyl)imide concentrated solution; disperse and crystallize to obtain a lithium bis(fluorosulfonyl)imide composition.

[0096] Comparative Example 2

[0097] Step 1) Dissolve KFSI in solvent c ethanol at room temperature to prepare a solution A with a concentration of 50%;

[0098] Step 2) Dissolve lithium chloride in solvent e ethanol at room temperature to prepare a solution B with a concentration of 50%;

[0099] Step 3) directly mixing solution A and solution B, stirring at room temperature after mixing, and then heating reaction, the heating reaction temperature is 30° C. After the reaction is completed, the reaction solution is filtered to filter out insoluble matter, the filtered solid is centrifuged and dried, and the filtrate is a crude solution of lithium bis(fluorosulfonyl)imide;

[0100] Step 4) concentrating the crude lithium bis(fluorosulfonyl)imide solution at normal pressure and then at reduced pressure, and then drying to obtain a crude lithium bis(fluorosulfonyl)imide solid;

[0101] Step 5) dissolving the crude solid of lithium bis(fluorosulfonyl)imide in step 4) into solvent d ethyl methyl carbonate to obtain solution D, wherein the dissolution temperature is 60°C and the concentration percentage of lithium bis(fluorosulfonyl)imide in solution D is 10%. Select a membrane filter with a pore size of 0.5 μm to filter solution D, collect the organic phase after solid-liquid separation, and concentrate and dry it to obtain a lithium bis(fluorosulfonyl)imide concentrated solution with a solution percentage concentration of 80%. Add a non-polar organic solvent xylene to the lithium bis(fluorosulfonyl)imide concentrated solution with a solution percentage concentration of 80%, wherein the mass of xylene added is 1.5 times the mass of the lithium bis(fluorosulfonyl)imide concentrated solution; disperse and crystallize to obtain a lithium bis(fluorosulfonyl)imide composition.

[0102] The lithium bis(fluorosulfonyl)imide compositions obtained in Examples 1-4 and Comparative Examples 1-2 were tested for ion content and organic solvent content in the compositions in the following manner.

[0103] Test part:

[0104] 1. Anion impurity analysis method

[0105] Equipment: Dionex ICS-900 Anion Test System

[0106] Analytical column: IP AG22 (4×50mm) + IP AS22 (4×250mm)

[0107] Chemical suppressor: AMMS 300 4mm

[0108] Eluent: Accurately draw 8.2mL 0.5mol / L Na 2 CO 3 +5.4mL 0.5mol / L NaHCO 3 Add to 1L ultrapure water, filter with water filter membrane (0.22μm), and remove bubbles with ultrasound (10min)

[0109] Sample testing: According to the Dionex ion chromatograph operating procedures, set the flow rate to 1.2 mL / min, flush the system with eluent until the instrument runs stably, set the instrument method, run for 15 min, and test the standards and samples.

[0110] Sample content calculation: Prepare the corresponding anion standard curve based on the standard solution test spectrum.

[0111] After the sample test is completed, manual integration is performed. According to the peak area corresponding to the ion in the test spectrum, the ion concentration is calculated from the standard curve, and finally the ion content is calculated.

[0112] 2. Cationic impurity analysis method

[0113] Ion chromatograph: Dionex ion chromatograph, cation test system;

[0114] Chromatographic column: CS16 cation analysis column (4×250mm) with CG16 guard column;

[0115] Suppressor: electrochemical suppressor;

[0116] Eluent: Pipette 4.5-4.75 mL (since the elution capacity of cationic eluent is affected by temperature, a larger amount should be taken at low temperature) of methanesulfonic acid into 2 L of ultrapure water, filter (if there is a 0.22 μm filter at the outlet of the ultrapure water machine, filtration is not necessary), and remove bubbles by ultrasound (20 min).

[0117] Cationic standard solution: Cationic mixed standard reagent (provided by Thermo), the concentration of the cationic mixed standard can be determined according to actual needs.

[0118] Sample determination: According to the Dionex ion chromatograph instrument operating procedures, set the flow rate to 1.0 mL / min, flush the system with eluent until the instrument runs stably, set the instrument method, run for 20 min, and test the standards and samples.

[0119] Calculation of cation concentration: Prepare the corresponding cation standard curve according to the standard solution test spectrum. After the sample test is completed, manually integrate. According to the peak area corresponding to the ion in the test spectrum, the ion concentration is calculated from the standard curve, and finally the ion content is calculated.

[0120] 3. Solvent residual analysis method: headspace method

[0121] Equipment: Agilent 6890

[0122] Chromatographic headspace system: Agilent 6890

[0123] Chromatographic column: HP-5 column, 30 m long, 0.32 mm internal diameter, 0.25 μm active phase thickness.

[0124] Chromatographic conditions: The oven was kept at 60°C for 2 minutes, then raised to 300°C at 30°C / min and kept at this temperature for 2 minutes.

[0125] Injection port temperature: 250°C, FID detection port temperature: 300°C.

[0126] Headspace conditions: 30 minutes at 80°C

[0127] Sampling: Dissolve 0.05g LiFSI in 200ml dimethyl sulfoxide (DMSO) aqueous solution, then add 2ml of 20% sodium chloride (NaCl) aqueous solution, and finally transfer the obtained solution to a sealed vial. DMSO: ultrapure water = 20:80 in DMSO aqueous solution

[0128] The specific test results of the ion and organic solvent contents in the lithium bis(fluorosulfonyl)imide compositions obtained in Example 1-4 and Comparative Example 1-2 are shown in Table 1.

[0129] Table 1 Parameters and test results of nitrate content in lithium bis(fluorosulfonyl)imide compositions

[0130]

[0131]

[0132] 4. Battery performance test method

[0133] The bis(fluorosulfonyl)imide lithium compositions prepared in the above Examples 1-4 and Comparative Examples 1-2 were applied to lithium ion battery electrolytes to prepare lithium ion batteries.

[0134] The positive electrode uses 622 ternary material, the negative electrode uses artificial graphite, the electrolyte solvent uses EC:EMC=3:7, the molar content of the lithium bis(fluorosulfonyl)imide composition in the electrolyte is 1 mol; based on the mass of the electrolyte as 100%, the mass percentage of FEC (fluoroethylene sulfate) is 3%. Among them, EC is ethylene carbonate and EMC is ethyl methyl carbonate.

[0135] A soft-pack battery with a capacity of 1Ah is prepared, and the preparation method of the soft-pack battery with a capacity of 1Ah adopts the existing technology.

[0136] The following performance tests were performed on the 1Ah capacity soft pack battery prepared above:

[0137] 1. High temperature cycle performance test: At 45°C, charge the formed battery with 1C constant current and constant voltage to the cut-off voltage, then charge it with constant voltage until the current drops to 0.05C, and then discharge it with 1C constant current to 3.0V. Repeat this cycle for 500 times, and record the first discharge capacity and the last discharge capacity.

[0138] The capacity retention rate of high temperature cycle is calculated as follows:

[0139] Capacity retention rate = last discharge capacity / first discharge capacity × 100%.

[0140] 2. Room temperature cycle performance test: At 25°C, charge the formed battery with 1C constant current and constant voltage to the cut-off voltage, then charge with constant voltage until the current drops to 0.05C, and then discharge with 1C constant current to 3.0V. Repeat this cycle for 800 times, and record the first discharge capacity and the last discharge capacity.

[0141] The capacity retention rate of high temperature cycle is calculated as follows:

[0142] Capacity retention rate = last discharge capacity / first discharge capacity × 100%.

[0143] The test results of the batteries prepared in Examples 1-4 and Comparative Examples 1-2 are shown in Table 2.

[0144] 3. Volume expansion rate: According to the above high temperature cycle performance test method, after the first week of charge and discharge cycle of the battery, test and record the volume V1 of the battery. After the 500th week of charge and discharge cycle of the battery, test and record the volume V2 of the battery. Calculate the battery 45°C high temperature cycle volume expansion rate according to the following formula:

[0145] The volume expansion rate after 500 cycles at 45°C = (V2-V1) / V1×100%.

[0146] Table 2 Electrical performance test results of Examples 1-4 and Comparative Examples 1-2

[0147]

[0148] By comparing Examples 1-4 with Comparative Example 1, it can be seen that the battery of Comparative Example 1 has a higher volume expansion rate after long-term high-temperature cycling. The possible reason is that the nitrate content in Comparative Example 1 is too high. During the long-term high-temperature cycling of the battery, the nitrate reacts to produce gas, increasing the volume expansion rate of the battery.

[0149] Compared with Comparative Example 2, the batteries of Examples 1-4 have higher capacity retention rates in normal temperature cycles and high temperature cycles. The possible reason is that the nitrate content of 20ppm-1000ppm in the lithium bis(fluorosulfonyl)imide composition can effectively inhibit the corrosion of lithium bis(fluorosulfonyl)imide to the electrode and improve the battery cycle performance.

[0150] By comparing Examples 1-4 with Comparative Examples 1-2, it can be seen that the batteries of Examples 1-4 have better room temperature cycle capacity retention and high temperature cycle capacity retention, and lower high temperature cycle volume expansion, indicating that in the lithium bis(fluorosulfonyl)imide composition, 20ppm-1000ppm of nitrate can not only effectively inhibit the corrosion of lithium bis(fluorosulfonyl)imide to the electrode and improve the cycle performance of the battery, but also a trace amount of nitrate can effectively reduce the long-term cycle volume expansion of the battery, reduce the risk of battery bulging, and improve the safety performance and stability of the battery. The above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A lithium bis(fluorosulfonyl)imide composition, characterized in that: The bis(fluorosulfonyl)imide lithium composition is applied to lithium battery electrolyte; The preparation method of the lithium bis(fluorosulfonyl)imide composition comprises the following steps: 1) KFSI is dissolved in solvent c to obtain solution A; 2) Lithium nitrate is dissolved in solvent e to obtain solution B; 3) Mixing solution A and solution B, stirring, and then heating to react. After the reaction is completed, filtering to obtain a crude solution of lithium bis(fluorosulfonyl)imide; 4) The crude lithium bis(fluorosulfonyl)imide solution in step 3) is passed through a cationic resin to remove cationic impurities, and then concentrated and dried for the first time to obtain a crude lithium bis(fluorosulfonyl)imide solid; 5) dissolving the crude solid of lithium bis(fluorosulfonyl)imide in step 4) into solvent d to obtain solution D, followed by filtering and washing with pure water, collecting the organic phase and concentrating and drying it for a second time, and finally adding a non-polar organic solvent for dispersion and crystallization to obtain a lithium bis(fluorosulfonyl)imide composition having a nitrate content of 20 ppm to 1000 ppm; The lithium bisfluorosulfonyl imide composition comprises lithium bisfluorosulfonyl imide and nitrate. Based on 100% of the total mass of the lithium bisfluorosulfonyl imide composition, the mass percentage of the lithium bisfluorosulfonyl imide is ≥99%.

2. The lithium bis(fluorosulfonyl)imide composition according to claim 1, characterized in that: In the step 1), the mass percentage of KFSI is 10% to 80% based on the mass of solution A as 100%; In the step 2), the mass percentage of lithium nitrate is 5% to 50% based on the mass of solution B as 100%; The heating temperature in step 3) is 20°C to 60°C, preferably 45°C to 60°C.

3. The lithium bis(fluorosulfonyl)imide composition according to claim 1, characterized in that: In the step 5), based on 100% of the mass of the solution D, the mass percentage of the lithium bis(fluorosulfonyl)imide is 5% to 80%; In the step 5), the crude solid of lithium bis(fluorosulfonyl)imide is dissolved in solvent d at a dissolution temperature of 10° C. to 80° C.

4. The lithium bis(fluorosulfonyl)imide composition according to claim 3, characterized in that: In the step 5), based on 100% of the mass of the solution D, the mass percentage of the lithium bis(fluorosulfonyl)imide is 15% to 50%; In the step 5), the crude solid of lithium bis(fluorosulfonyl)imide is dissolved in solvent d at a dissolution temperature of 20° C. to 60° C.

5. The lithium bis(fluorosulfonyl)imide composition according to claim 1, characterized in that: The first concentration and drying in step 4) includes first concentration at normal pressure and then concentration at reduced pressure; The mass of pure water in the pure water washing in step 5) is 0.5 to 5 times the mass of the crude solid product of lithium bis(fluorosulfonyl)imide; the number of pure water washing is ≥ 1 times, and the pure water washing step is to further remove potassium nitrate dissolved in water and reduce the nitrate content of the lithium bis(fluorosulfonyl)imide composition; After the second concentration and drying in step 5), the mass percentage of lithium bis(fluorosulfonyl imide) is 60% to 90% based on the mass of the lithium bis(fluorosulfonyl imide) concentrate as 100%; the mass of the non-polar organic solvent added is 0.5 to 3 times the mass of the lithium bis(fluorosulfonyl imide) concentrate; In the step 5), a membrane filter is used for filtration, and the membrane pore size of the membrane filter includes at least one of 2um, 1um or 0.1-0.5um.

6. The lithium bis(fluorosulfonyl)imide composition according to claim 1, characterized in that: The solvent c and the solvent e each independently include one or more of anhydrous methanol, ethanol, acetone, ether, ethyl acetate, butyl acetate, sec-butyl acetate, amyl acetate, n-hexyl acetate, dimethyl carbonate, and ethyl methyl carbonate; The solvent d is a hydrophobic polar aprotic solvent, including one or more of a carbonate solvent or a nitrile solvent; The cationic resin includes a strong acid resin; The non-polar organic solvent includes one or more of dichloromethane, dichloroethane, toluene, xylene, and cyclohexane.

7. The lithium bis(fluorosulfonyl)imide composition according to claim 1, characterized in that: Based on 100% of the total mass of the lithium bis(fluorosulfonyl)imide composition, the content of the nitrate ion is 20 ppm to 500 ppm.

8. The lithium bis(fluorosulfonyl)imide composition according to claim 1, characterized in that: Based on 100% of the total mass of the lithium bis(fluorosulfonyl)imide composition, the mass content of the lithium bis(fluorosulfonyl)imide is ≥99.8%.

9. The lithium bis(fluorosulfonyl)imide composition according to claim 1, characterized in that: The lithium bis(fluorosulfonyl)imide composition further comprises K + , H2O, an organic solvent, based on 100% of the total mass of the lithium bis(fluorosulfonyl)imide composition, the K + ≤5ppm, the H2O≤50ppm, and the organic solvent≤1500ppm.